PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN NON PERFORMING LOAN (NPL) TERHADAP RETURN ON ASSETS (ROA) PADA BANK UMUM SWASTA NASIONAL (BUSN) DEVISA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Widia Sinta Sinta; Makhdalena '; RM.Riadi Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was conducted to examine the effect of the Capital Adequacy Ratio (CAR) and the Non Performing Loan (NPL) to Return on Assets (ROA). Sample in this study are 22 National Private Banks (BUSN) Foreign exchange listed in the Indonesia Stock Exchange which the research period 2009-2013. The type of data used is quantitative data. Data analysis technique using multiple linear analysis, t test and F test with significance level of 0.05%. The result showed that the Capital Adequacy Ratio (CAR) and the Non Performing Loan (NPL) simultaneously affect the Return on Assets (ROA). It is based on the results of the analysis, which shows the calculation result Fcount > Ftable (11.093> 3.08). Furthermore, the partial results of the study show the Capital Adequacy Ratio (CAR) effect on Return on Assets (ROA). This is evidenced by the t test where the variable tcalculation 4.086 to 1.659 ttabel value. This shows that tcount > ttable. As for the Non Performing Loan (NPL) shows that Non Performing Loan (NPL) have an influence on the Return on Assets (ROA). This is evidenced by the t test where t count variable with the value ttabel -1.659 and tcount-2.402. This shows that -tcount < -ttable. Predictive ability of both variables on Return on Assets (ROA) in this study only 17.2%, while the remaining 82.8% is affected by other factors not included in the model study. Keywords: Return on Assets (ROA), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL)